Long-term experiences with the two-stage palatoplasty with regard to the development of maxillary arch - Fára, M; Brousilová, M; Hrivnáková, J; Tvrdek, M (Acta chirurgiae plasticae, 1992)
From our data on 46 patients operated on by one surgeon in 1961 and 1962 who were regularly examined up to adulthood, it may be concluded that the growth results of the two-stage palatoplasty, when the second stage is done before the patient is 7 years of age, are almost identical to the results of one-stage palate repair performed at the age of 3 to 4 years. However, a greater orthodontic effort is needed to achieve a properly aligned dentoalveolar arch with the two-stage palatoplasty.
Keywords: Cleft Palate; rozštěp patra; Infant; Male; Surgical Procedures, Operative; lidé; longitudinální studie; Humans; Child; chirurgie operační; processus alveolaris; Child, Preschool; Alveolar Process; mužské pohlaví; Longitudinal Studies; kojenec; zubní oblouk; dítě; Dental Arch; ženské pohlaví; Female; předškolní dítě